2006
DOI: 10.2166/wst.2006.379
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of activated sludge in a sequencing batch reactor for polyhydroxyalkanoate production

Abstract: The paper describes the start up of a process for the production of polyhydroxyalkanoates (PHAs) from activated sludge. The excess sludge from a wastewater treatment plant was inoculated in a lab-scale sequencing batch reactor (SBR) to be enriched under aerobic conditions through intermittent feeding with a mixture of organic acids. Enriching of activated sludge was monitored through the measurement of polymer concentrations either in the mixed liquor or in the microbial biomass. The bacterial population dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…The obtained yields of polymer on substrate consumed were fallen in the same range with those obtained by Majone et al [6] (0.37-0.41 g COD PHA g -1 COD S), Dionisi et al [3] (0.32-0.66 g COD PHA g -1 COD S), Serafim et al [8] (0.37-0.83 g COD PHA g -1 COD S), and were slightly higher than those observed by Bengtsson et al [9] (0.08-0.27 g COD PHA g -1 COD S). Increase in storage yield for increased acetate concentrations were observed before [8].…”
Section: Effect Of Substrate Loading On Polymer Accumulationsupporting
confidence: 87%
See 1 more Smart Citation
“…The obtained yields of polymer on substrate consumed were fallen in the same range with those obtained by Majone et al [6] (0.37-0.41 g COD PHA g -1 COD S), Dionisi et al [3] (0.32-0.66 g COD PHA g -1 COD S), Serafim et al [8] (0.37-0.83 g COD PHA g -1 COD S), and were slightly higher than those observed by Bengtsson et al [9] (0.08-0.27 g COD PHA g -1 COD S). Increase in storage yield for increased acetate concentrations were observed before [8].…”
Section: Effect Of Substrate Loading On Polymer Accumulationsupporting
confidence: 87%
“…Under transient conditions, such as feast/famine or anaerobic/aerobic, growth becomes unbalanced and PHA accumulating ability of mixed cultures increase. A three-step process is proposed by many researchers [3,6,7] for PHA production, of which first step was production of organic acids. The second step of the process was enrichment and production of biomass with high storage ability.…”
Section: Introductionmentioning
confidence: 99%
“…However, on operational day 271 Meganema decreased to 4.95–6.93% of the population, while Zoogloea was the only genus >10% (and only in reactor AE-12). Though Meganema has been observed in other ADF enrichment SBRs wherein PHA was synthesized in excess (Hanson et al 2016, Majone et al 2006), including with fermented dairy manure as a substrate (Hanson et al 2016), the high abundance of Meganema was in contrast to other ADF studies that reported dominant genera including Thauera (Albuquerque et al 2013, Carvalho et al 2014, Lemos et al 2008), Azoarcus (Bengtsson et al 2010a, Bengtsson et al 2010b, Waller et al 2012), or Plasticicumulans (Jiang et al 2011, Jiang et al 2012, Marang et al 2013). Additionally, most of the genera identified in this study present at >1% (e.g., Leadbetterella , Haliscomenobacter, Aquabacterium, Luteimonas, Hydrogenophaga, Thermomonas, Mycobacterium, Filomicrobium, Dokdonella, Hylemonella, Pseudofulvimonas, Mesorhizobium, Hyphomicrobium, Parvibaculum, Brevundimonas, Novosphingobium, Sphingomonas, Altererythrobacter, Xanthobacter, Gp6, and Gp4 ) have not been reported in other ADF investigations; Amaricoccus and Paracoccus have only been nominally present in ADF systems (Lemos et al 2008, Queirós et al 2014).…”
Section: Resultsmentioning
confidence: 81%
“…(30,31) were found able to store PHA in axenic cultures. In relation to FlaVobacterium sp., it has been isolated from activated sludge (32) and has been detected, by this research group, in a different mixed culture showing PHA storage response under feast and famine regime (27). The Cytophaga-FlaVobacterium group has been studied in relation to PHA production under anaerobic/aerobic conditions (33).…”
Section: Effect Of Length Of Cycle On Storage Versus Growthmentioning
confidence: 96%